Renal outcomes of treatment with telmisartan in patients with stage 3–4 chronic kidney disease: A prospective, randomized, controlled trial (JINNAGA) - Kitamura, Mineaki (SAGE Open Med, 2020)
OBJECTIVES: Although angiotensin II receptor blockers are effective for patients with chronic kidney disease, dose-dependent renoprotective effects of angiotensin II receptor blockers in patients with moderate to severe chronic kidney disease with non-nephrotic proteinuria are not known. Our aim was to elucidate the dose-dependent renoprotective effects of angiotensin II receptor blockers on such patients. METHODS: A multicenter, prospective, randomized trial was conducted from 2009 to 2014. Patients with non-nephrotic stage 3–4 chronic kidney disease were randomized for treatment with either 40 or 80 mg telmisartan and were observed for up to 104 weeks. Overall, 32 and 29 patients were allocated to the 40 and 80 mg telmisartan groups, respectively. The composite primary outcome was renal death, doubling of serum creatinine level, transition to stage 5 chronic kidney disease, and death from any cause. Secondary outcomes included the level of urinary proteins and changes in the estimated glomerular filtration rate. RESULTS: There was no difference in the primary outcome (p = 0.78) and eGFR (p = 0.53) between the two groups; however, after 24 weeks, urinary protein level was significantly lower in the 80 mg group than in the 40 mg group (p < 0.05). No severe adverse events occurred in either group, and the occurrence of adverse events did not significantly differ between them (p = 0.56). CONCLUSION: Our findings do not demonstrate a direct dose-dependent renoprotective effect of telmisartan. The higher telmisartan dose resulted in a decrease in the amount of urinary protein. Even though high-dose angiotensin II receptor blockers may be preferable for patients with stage 3–4 chronic kidney disease, the clinical importance of the study results may be limited. The study was registered in the UMIN-CTR (https://www.umin.ac.jp/ctr) with the registration number UMIN000040875.